Citizenship Education Study of Illegal Parking in Abepura, Jayapura City - Willius Kogoya; Nikson E Aronggear (International Journal of Educational Research Excellence (IJERE), 2022)
Good citizens will not do anything that can harm the State even though it is related to personal needs. This study examines the citizenship review of illegal parking in the city of Jayapura, which is detrimental to the state because parking fees are not included in regional income but for personal interests, and this shows the low awareness of being a good citizen. With a qualitative method, this study aims to reveal the causes of rampant illegal parking, the problems that arise, and how local governments respond to them. The sample selected was ten people consisting of five illegal parking officers, three official parking officers, and two officers from the Jayapura City Regional Revenue Service. From the results of the study obtained information that illegal parking in the city of Jayapura is caused by factors: urgent needs, lack of job opportunities, and lack of human resource skills. The impact is a decrease in regional income and inconvenience in the parking area. There are no less illegal parking attendants who act arrogantly, asking for money by force in excess of the parking fee that should have been even though he did not carry out his duties to regulate vehicles that were parked properly. The Regional Government has taken several actions, including controlling parking locations, providing counseling to illegal parking officers, placing official parking officers, and inviting illegal parking officers to register themselves as official parking officers.